PWE-045 Vedolizumab results in reduced hospitalisation and steroid use over 1-year:results from the scottish vedolizumab cohort. (8th June 2018) - Plevris, Nikolas; Chuah, Cher; Jenkinson, Phil; Allen, R; Baker, P; Brennan, Paul; Churchhouse, Antonia; Din, S; Donoghue, Emma; Gaya, Daniel; Groome, Max; Jafferbhoy, H; et al.
Abstract : Introduction: The GEMINI trials and an increasing body of real-world data have demonstrated the effectiveness and safety of vedolizumab (VDZ) in IBD. However, there is limited available data about its effect on hospitalisations and steroid use. Our aim was to address this in a large real-world cohort of IBD patients from across Scotland. Methods: A multicenter retrospective cohort analysis of medical records was performed across 7 Scottish healthcare trusts. Primary outcomes were hospitalisation rates and overall steroid use in patients remaining on VDZ. Secondary outcomes were safety and intention to treat steroid free remission rates in patients with active disease. All data were prospectively collected as part of routine clinical care. Baseline demographics, clinical scores (HBI or Partial Mayo), faecal calprotectin (FC), endoscopy and radiology at 3, 6 and 12 months was recorded where available. Active disease was defined as endoscopic or radiographic evidence of disease or FC >200 mcg/g. Clinical remission was defined as HBI <5 or Partial Mayo<2. Biochemical remission was defined as FC <200 mcg/g. Results: 340 (137 UC and 203 CD) patients were included in the primary analysis with a median follow-up of 9.4 months. Hospitalisation rates per patient-year were 0.60, 0.67, 0.36 and 0.16 at baseline, 3, 6 and 12 months of treatment respectively. Total number of hospitalisations reduced by 52.5% from 204 (12 months prior to VDZ) to 97 (12 months after VDZ). Proportion of patients on concomitant steroids reduced from 39.7% to 16.7% (n=332), 8.1% (n=270), 9.3% (n=194) at 3, 6 and 12 months respectively. In patients with active CD (n=153, 75.4%) steroid free clinical and steroid free biochemical remission rates were; 54.4% and 30.2% at 3 months; 47.7% and 32.1% at 6 months; 28.6% and 33.9% at 12 months. In patients with active UC (n=112, 81.8%) steroid free clinical and steroid free biochemical remission rates were; 57.4% and 40.9% at 3 months; 51.6% and 39.1% at 6 months; 37.5% and 41.2% at 12 months. Our cohort received >2066 VDZ infusions, 2 (0.6%) patients developed infusion reactions, 9 (2.6%) patients developed serious infections and 17 (5.0%) serious adverse events. Conclusions: VDZ is associated with reduced hospitalisation and steroid use over 1 year. Steroid free remission rates and safety profile is in keeping with the published literature.